Magnetically controlled single-electron shuttle - Ilinskaya, O.A.; Kulinich, S.I.; Krive, I.V.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
A theory of single-electron shuttling in an external magnetic field in nanoelectromechanical system withmagnetic leads is presented. We consider partially spin-polarized electrons in the leads and electron transport in both the Coulomb blockade regime and in the limit of large bias voltages when the Coulomb blockade is lifted. The influence of the degree of spin polarization on shuttle instability is considered. It is shown that there is certain degree of spin polarization above which the magnetic field ceases to control electron transport. In the Coulomb blockade regime the dependence of the threshold magnetic field, which separates the “shuttle” and vibron regimes, on the degree of polarization is evaluated. The possibility of re-entrant transitions to the shuttle phase is discussed.